ANALISIS KEMAMPUAN RUTIN DALAM PEMBIAYAAN PEMBANGUNAN KABUPATEN TEBO TAHUN 2008 - 2012 - Fairuz, Fairuz (Jurnal Dinamika Manajemen, 2023)
This study entitled Analysis of Routine Capability in Tebo District Development Financing under the guidance of Drs. Adi Bhakti. SE., M.Sc. This study aims to determine Routine Capability is one of the basic capital of local government in financing regional expenditures, as measured by the Routine Capability Index ratio. The analysis technique used is through descriptive qualitative analysis. The results of this study indicate that with the growth of Local Own Revenue of 16.01% per year and the average growth rate of Regional Expenditure in Tebo Regency of 10.92% so that during the period 2008 - 2012 the ratio of ability index routine of 3.58% and this means that Regional Original Income (PAD) has a low ability to finance routine expenses.